Numerical simulation on the heat transfer characteristics of two-phase loop thermosyphon with high filling ratios. (March 2022) - Wang, Kuiming; Hu, Chengzhi; Jiang, Bo; Hu, Xianfeng; Tang, Dawei
Highlights: Heat transfer mechanism of TPLT with high filling ratio is revealed. Pool boiling is changed into flow boiling with filling ratio increases. Heat transfer performance positively correlates with the circulation velocity. For high filling ratios, thermal resistance decreases with heat input increases. Abstract: The two-phase loop thermosyphon (TPLT) with a high filling ratio is considered an efficient heat transfer device and therefore has a good application prospect in the field of high heat flux dissipation engineering. However, the heat transfer mechanism of the TPLT with high filling ratios remains elusive. In this study, we establish a computational fluid dynamics (CFD) model of the loop thermosyphon. In order to accurately simulate boiling and condensation processes, we take into account the relationship between saturation temperature and pressure in the phase change model. There were two flow patterns, i.e., the bubbly flow and the slug flow, under low filling ratios in the heating section, in which the pool boiling dominates the main heat transfer mechanism, and dropwise condensation occurred in the condensation section. The driving force to propel the liquid during the vapor bubbles rise cannot be transferred to the liquid in the right tube, resulting in lower flow velocity. In stark contrast, the single-phase flow and the bubbly flow occurred periodically in the loop thermosyphon with high filling ratios, in which the dominant heat transfer mechanism is the flow boiling. The rising bubbles promote the clockwise flow of liquid in the loop like a pump. Because of the switch of the heat transfer mechanism, the average flow velocity increased, and the thermal resistance decreased. The minimum thermal resistance was 0.15 K/W under a filling ratio of 75%, and the maximum average velocity of the fluid was 0.19 m/s. Furthermore, we found a strong coupling relationship between the heat transfer performance and the flow characteristics of the loop thermosyphon. For low filling ratios, local dry-out occurred in the loop thermosyphon under a high input heat flux, leading to an increase in the thermal resistance. For high filling ratios, the average velocity of the fluid was augmented with the increase in heating power, while the liquid was capable of being replenished quickly in the heating section to avoid the dry-out. Therefore, the loop thermosyphon with high filling ratios enables a better heat transfer performance under a high heat flux than those with low filling ratios.